2020
DOI: 10.1136/bmjopen-2020-038473
|View full text |Cite
|
Sign up to set email alerts
|

Which aspects of neighbourhood environment are most associated with meeting physical activity recommendations in American adults: an NHIS study

Abstract: ObjectivesTo investigate which perceived neighbourhood characteristics are most strongly linked with adequate physical activity (PA) in a nationally representative sample of adults in the USA.DesignCross-sectional.SettingUSA via 2015 National Health Interview Survey Data.ParticipantsA group of 28 697 non-institutionalised adults with complete data.Primary outcome measuresMeeting PA was defined as 150 min/week of moderate to vigorous activity.ResultsThe population had a mean age of 49.6 (±18.3) years and was 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…25,34 Environment (Built) In NHIS (2015), the odds of meeting aerobic guidelines were higher among participants who perceived more walkable infrastructure such as having places to walk, available bus and transit services, and availability of streets with sidewalks according to self-reported questionnaire data. 40 These findings are aligned with the Community Preventive Services Task Force 2016 report that transportation systems with street connectivity, activity-friendly (pedestrian and bicycle) routes, and close proximity and access to parks and recreational facilities are associated with higher physical activity. 41 Environment Weather and Air Quality Evidence consistently indicates that adverse weather or air quality is associated with lower physical activity.…”
Section: Urbanizationsupporting
confidence: 58%
See 1 more Smart Citation
“…25,34 Environment (Built) In NHIS (2015), the odds of meeting aerobic guidelines were higher among participants who perceived more walkable infrastructure such as having places to walk, available bus and transit services, and availability of streets with sidewalks according to self-reported questionnaire data. 40 These findings are aligned with the Community Preventive Services Task Force 2016 report that transportation systems with street connectivity, activity-friendly (pedestrian and bicycle) routes, and close proximity and access to parks and recreational facilities are associated with higher physical activity. 41 Environment Weather and Air Quality Evidence consistently indicates that adverse weather or air quality is associated with lower physical activity.…”
Section: Urbanizationsupporting
confidence: 58%
“…In the self-reported NHIS (2015) data, the odds of meeting aerobic guidelines for physical activity were 16% lower if weather was perceived as a consistent barrier. 40 In BRFSS data (2003–2011), the odds of reporting no participation in physical activity were higher when participants lived in areas with extreme hot or cold temperatures or high precipitation. 38 In terms of air pollution, 2001 and 2003 to 2011 BRFSS data indicated that higher air pollution was associated with higher levels of physical inactivity.…”
Section: Physical Activity Levels By Risk Factors For Poor Cvhmentioning
confidence: 98%
“…Physical activity can lessen severe joint pain and disability and benefit the physical and mental health of individuals with arthritis 11 . However, adults’ ability to engage in physical activity is partly determined by their access to the built and social environment 8,32 . A neighborhood's walkability and presence of transit stops, libraries, museums, and movies were associated with adults meeting physical activity recommendations of 150 minutes of moderate to vigorous physical activity per week 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neighborhood social cohesion, the physical conditions of a neighborhood—such as the presence or absence of hazards—also shape opportunities for PA. Previous research has identified environmental predictors of PA across the lifespan, including access to facilities or services (Gebauer et al, 2020b; Ranchod et al, 2014), access to public transportation (Gebauer et al, 2020b), walkability (Gebauer et al, 2020a; King et al, 2011; Kwarteng et al, 2014; Orstad et al, 2018) vandalism/littering (Strong et al, 2013), and traffic (Chaudhury et al, 2012). For example, Chaudhury et al (2012) found that accessible seating and sidewalks that are even, wide, and well-lit promote PA in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Of those studies that have examined the relationships between PA and the neighborhood environment (Chaudhury et al, 2016; Gebauer et al, 2020a; Gebauer et al, 2020b; Kwarteng et al, 2014; Mendes de Leon et al, 2009; Mooney et al, 2017; Murillo et al, 2016; Quinn et al, 2019; Ranchod et al, 2014; Strong et al, 2013; Whitaker et al, 2019; Yi et al, 2016), only a few utilized longitudinal designs (Mendes de Leon et al, 2009; Mooney et al, 2017). Lack of evidence from longitudinal designs challenges the ability to ascertain the direction of a relationship between the neighborhood environment and PA. To address the gaps discussed above, the present study examined the associations between perceptions of the neighborhood environment and PA among a nationally representative sample of US adults aged 50 and older.…”
Section: Introductionmentioning
confidence: 99%